2015
DOI: 10.1177/1740774515589592
|View full text |Cite
|
Sign up to set email alerts
|

Risks and benefits of trial participation: A qualitative study of participants’ perspectives in Russia

Abstract: The risk-benefit assessment as performed by most interviewed trial participants involved multiple components, including the ones unrelated to the trial itself, and was largely context-dependent. Perspectives of research participants can enrich frameworks for the evaluation of trial risks and benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…The gaining of knowledge through research participation was mentioned 16 times overall, ranked in the top three reasons four times, and was given as the top reason in one paper to participate . Knowledge was ranked fifth in Sub‐Saharan Africa and Eastern Europe, in HIV research, by male and patient participants and for hypothetical studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gaining of knowledge through research participation was mentioned 16 times overall, ranked in the top three reasons four times, and was given as the top reason in one paper to participate . Knowledge was ranked fifth in Sub‐Saharan Africa and Eastern Europe, in HIV research, by male and patient participants and for hypothetical studies.…”
Section: Resultsmentioning
confidence: 99%
“…The gaining of knowledge through research participation was mentioned 16 times overall, [25,27,41,44,54,59,60,62,67,73,76,81,82,[86][87][88] ranked in the top three reasons four times, [44,59,67,88] and was given as the top reason in one paper to participate [44]. Knowledge was ranked fifth in Sub-Saharan Africa and Eastern Europe, in [20,32,36,69,78], and ranked sixth overall.…”
Section: Knowledgementioning
confidence: 99%
“…Conversely, a study in Tunisia (Bouida et al 2016) found that most participants in medical research were motivated by altruism. In Russia, a study (Zvonareva et al 2015) into the risks and benefits of trial participation found that those with higher healthcare needs were more willing to participate in studies that provide some form of free treatment, such as regular check-ups, individual test results or access to a physician (Zvonareva et al 2015). Gatny and Axinn (2012) reported that pregnant women in the United States were more likely to participate in research if they expected to learn more about pregnancy health and get a free medical test, than if they were to receive a monetary payment.…”
Section: Reimbursementmentioning
confidence: 99%
“…, Zvonareva et al . ). Without established principles in this regard, it remains incumbent on the individual researcher to follow local institutional and study‐specific protocols to ensure that the requirement for voluntary participation is met and that consent is obtained without coercion (Ripley , Wertheimer & Miller ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation